Come my staff, I lean upon you: an iconographic and contextual study of sticks and staves from 18th dynasty Egypt - Brown, Nicholas R (AUC Knowledge Fountain, 2015)
Sticks and staves are some of ancient Egypt’s most versatile tools: they can function as badges of status, walking aids, tools for farmers, weapons for guards, or any combination of these. Though earlier studies have examined the names and types of staves from all periods of ancient Egypt, no former scholarship has exclusively examined the ways in which sticks are used in tomb decoration from the 18th Dynasty. By looking at how the staves are used in elite tomb decoration, one is able to understand how the staff had both a practical use as well as symbolic meaning associated with it. The current study focuses on elite tomb decoration from the 18th Dynasty necropoleis of Memphis, Amarna, Thebes, and el-Kab. What follows is a survey of known 18th Dynasty staves, either from excavated contexts or museum collections, to see how the physical evidence matches with what is depicted in the tombs, as well as to understand the role of this artifact within ancient Egyptian burials during the 18th Dynasty. Results indicate that some sticks served multiple purposes: used as a sign of social rank, but also as a tool with which to punish or protect. Other sticks, however, are used exclusively as funerary offerings or badges of status for the figure carrying them. Additionally, it has been found that officials, after death, carry both the mdw staff and the wAs scepter to indicate their divine transformation. This is due to the staves’ associations with the cardinal directions, embalming tents, and/or their frequent use by deities. The physical survey of sticks shows that staves were an important part of the burial of the deceased, and that they were either purpose-made funerary offerings or daily life objects which were then ritually transformed into sacred items. The deceased, in the afterlife, used their sticks to aid in achieving divine status, traverse the path between this world and the next, and to indicate their authority amongst the dead.